E-learning communication skills training for physiotherapy students: A two phased sequential mixed methods study. Issue 8 (August 2021) - Soundy, Andy; Hemmings, Laura; Gardiner, Lucy; Rosewilliam, Sheeba; Heneghan, Nicola R.; Cronin, Katie; Reid, Kate
Highlights: E-learning can enhance confidence when approaching distressing interactions. A single e-learning communication skills session can have sustained benefit. Research is needed to determine the impact across different clinical environments. Abstract: Objective: Test whether a single e-learning session can improve empathy and communication across pre-registration and postgraduate physiotherapy students. Methods: Design: Two-phase sequential mixed methods study. Phase 1: Pilot randomised control trial. Phase 2: Qualitative study using interpretive phenomenological analysis. Sampling: A purposive sample for both phases. Outcome measures: Phase 1: At baseline, post and 6-week follow up. Demographics. Primary outcome: Inter-personal Reactivity Index (IRI). Phase 2: Demographics and interview schedule. Intervention: An e-learning (E) narrative intervention group or active control condition. Analysis: Phase 1: Descriptive statistics and confidence intervals. Mann-Whitney U test to compare across group change. Phase 2: Thematic analysis. Results: Thirty-nine participants took part in the mixed methods study (Phase 1 n = 25; Phase 2 n = 14). Phase 1: No significant differences between groups were identified. Potentially importance changes across time were found for the intervention group and control group. Phase 2 results identified 5 themes and 12 sub-themes. Conclusion: The e-learning groups identified an increase in the perceived ability to handle distressing communication. Other important findings from the e-learning are discussed. Further research is warranted. Practical Implications Novel e-learning intervention may have an important role in curriculum development and clinical practice to promote therapeutic communication. Practical Implications: Novel e-learning intervention may have an important role in curriculum development and clinical practice to promote therapeutic communication.